2020
DOI: 10.3389/fpls.2020.00855
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic and Hydrophilic Extractives in Norway Spruce and Kurile Larch and Their Role in Brown-Rot Degradation

Abstract: Extractives found in the heartwood of a moderately durable conifer (Larix gmelinii var. japonica) were compared with those found in a non-durable one (Picea abies). We identified and quantified heartwood extractives by extraction with solvents of different polarities and gas chromatography with mass spectral detection (GC-MS). Among the extracted compounds, there was a much higher amount of hydrophilic phenolics in larch (flavonoids) than in spruce (lignans). Both species had similar resin acid and fatty acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…The result exhibited that the polar solvent acetone has higher efficiency for A. confusa heartwood extraction. Previous studies [ 54 , 55 , 56 , 57 , 58 ] also indicate that polar solvents are more efficient in heartwood extraction than non-polar solvents. In addition, the extracts obtained from polar solvents extraction are mostly composed of polar compounds.…”
Section: Resultsmentioning
confidence: 95%
“…The result exhibited that the polar solvent acetone has higher efficiency for A. confusa heartwood extraction. Previous studies [ 54 , 55 , 56 , 57 , 58 ] also indicate that polar solvents are more efficient in heartwood extraction than non-polar solvents. In addition, the extracts obtained from polar solvents extraction are mostly composed of polar compounds.…”
Section: Resultsmentioning
confidence: 95%
“…The extractives of paulownia wood had no or marginal inhibitory effect on T. palustris and G. trabeum and honey mesquite extractives were not effective against I. lacteus . Füchtner et al [ 104 ] showed that the resistance of non-durable Norway spruce heartwood to brown-rot fungus R. placenta results from the presence of fungitoxic hydrophobic resin, while in the case of moderately durable Kurile larch heartwood, the resistance is due to large amounts of different antioxidant flavonoids.…”
Section: Antifungal Substances Of Plant Originmentioning
confidence: 99%
“…Wood extractives play an essential role in protecting living trees against fungal attacks and other pests like insects [19]. Especially phenolic extractives and resin acids act as natural fungicides of trees [12,194]. The extract of Delonix regia (also known as flame tree or flamboyant) in the study of Salem et al [195] showed inhibition of fungal growth and antioxidant activity.…”
Section: Utilization Of Wood Extractivesmentioning
confidence: 99%